2020
DOI: 10.3389/fneur.2020.575075
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Non-invasive Brain Stimulation Applications to Memory in Healthy Aging

Abstract: It has long been acknowledged that memory changes over the course of one's life, irrespective of diseases like dementia. Approaches to mitigate these changes have however yielded mixed results. Brain stimulation has been identified as one novel approach of augmenting older adult's memory. Thus far, such approaches have however been nuanced, targeting different memory domains with different methodologies. This has produced an amalgam of research with an unclear image overall. This systematic review therefore ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 108 publications
(170 reference statements)
0
17
0
Order By: Relevance
“… 14 , 16 Recent research suggests that other cognitive tasks or domains, such as episodic memory, may be more amenable to atDCS‐induced improvements during or immediately after intervention. 6 , 11 , 28 With regard to the stimulation protocol, there is no consent yet about the efficacy of specific parameters over others, leaving the question of optimal stimulation intensity and electrode configuration unresolved. Previous studies have applied the same (1 mA) or higher intensities (1.5 or 2 mA) with the same (left prefrontal) or other electrode configurations (bilateral frontal, right prefrontal) with mixed evidence overall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 16 Recent research suggests that other cognitive tasks or domains, such as episodic memory, may be more amenable to atDCS‐induced improvements during or immediately after intervention. 6 , 11 , 28 With regard to the stimulation protocol, there is no consent yet about the efficacy of specific parameters over others, leaving the question of optimal stimulation intensity and electrode configuration unresolved. Previous studies have applied the same (1 mA) or higher intensities (1.5 or 2 mA) with the same (left prefrontal) or other electrode configurations (bilateral frontal, right prefrontal) with mixed evidence overall.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 15 With regard to electrode configuration, a recent review suggests that simultaneous targeting of multiple nodes of the frontoparietal network with tDCS during cognitive training may be needed to produce benefits on the behavioral level in older adults. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Combined interventions of tDCS and cognitive training present a promising means to counteract cognitive impairments in healthy as well as in pathological aging (Berryhill & Martin, 2018 ; de Sousa et al, 2020 ; Goldthorpe et al, 2020 ). Improved understanding of targeted neuronal network effects of combined interventions in older adults will therefore inform the development of specific therapeutic interventions against age‐associated cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial direct current stimulation (tDCS), especially when applied over multiple sessions and combined with training interventions, has emerged as a promising means to modulate cognitive functions in younger adults, older adults, and clinical populations (Berryhill & Martin, 2018 ; Goldthorpe et al, 2020 ; Polania et al, 2018 ). However, neural mechanisms underlying such improvements are poorly understood (Berryhill & Martin, 2018 ; Horne et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all NIBS studies that targeted two regions in healthy older adults significantly improved WM outcomes ( Park et al, 2014 ; Arciniega et al, 2018 ; Borghini et al, 2018 ; Reinhart and Nguyen, 2019 ), while those that targeted one region showed mixed results ( Goldthorpe et al, 2020 ). Therefore, it is reasonable to call for studies targeting two regions, both in healthy participants and in patients with schizophrenia, depression, dementia, MCI, etc.…”
Section: Future Directions and Limitationsmentioning
confidence: 99%